Fungsi Bahasa dalam Lelakaq Sasak - Yudi H. Himawan (Balai Bahasa Provinsi Papua, 2019)
This paper attempts to depict the function of language in lelakaq of Lombok society. Lelakaq is one of local wisdom in Lombok island. The data collection used observation and interview method, besides, the researcher as the native speaker of Sasak also applied introspective method, which is used by sinergizing the understanding of lelakaq.From the study, it can be found that lelakaq of Sasak has enormous function, used as a guidance and controller to behave in every day life of Sasak people. Among those function, there are moral values, and also education, religious, another wisdom values in life.